Aluminum color test report for SF portion (RFA-003_Rev D) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of aluminum color test report for shop front portion.